2017
DOI: 10.22159/ajpcr.2017.v10i11.20766
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Active Compounds in Kalanchoe Pinnata (Lmk) Pers Ethyl Acetate Fraction on Lupus Arthritis Mice

Abstract: Objective: The aim of this research was to measure the effects of the ethyl acetate fraction of Kalanchoe pinnata (Lmk) Pers (EF-KP) on lupus arthritis mice. Methods:The research was performed by testing of CD123 + interferon-α (IFN-α + ) dendritic cells and CD68 + interleukin 6 (IL-6 + ) macrophages as the main biomarkers using flow cytometry method, and then, the outcomes were directly observed in the joint's tissue structure. The results of the research were analyzed using statistics. Results IL-6+ macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some identified publications focused on the immunomodulatory effect of B. pinnatum extracts and compounds. In lupus mice, B. pinnatum reduced T cell activation ( Indriyanti et al, 2018b ) and B cell maturation, decreased production of TNF-α ( Dantara et al, 2021 ) and improved histopathological nephritis markers ( Indriyanti et al, 2018a ). In addition, the aqueous extract and the flavonoid quercetin reduced in vitro mast cell activation and in vivo airway inflammation in allergic airway models ( Cruz et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some identified publications focused on the immunomodulatory effect of B. pinnatum extracts and compounds. In lupus mice, B. pinnatum reduced T cell activation ( Indriyanti et al, 2018b ) and B cell maturation, decreased production of TNF-α ( Dantara et al, 2021 ) and improved histopathological nephritis markers ( Indriyanti et al, 2018a ). In addition, the aqueous extract and the flavonoid quercetin reduced in vitro mast cell activation and in vivo airway inflammation in allergic airway models ( Cruz et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through topological research, the essential pharmaceuticals for the treatment of diabetes derived from K. pinnata were determined. Furthermore, the authors have verified the existence of diverse bioactive substances in the leaf extract of this plant, particularly abundant in quercetin, a flavonoid known for its remarkable efficacy in reducing lupus arthritis in a mouse model ( Indriyanti et al, 2017 ). As per the findings of ( Ogidigo et al, 2022 ) ethyl acetate fractions of K. Pinnata contains significant amounts of quercetin, luteolin, isorhamnetin, and luteolin-7-glucoside, the extract exhibited a reduction in an oxidative imbalance in rats subjected to neurotoxicity induced by aluminium chloride; these results indicate a potential neuroprotective effect.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the importance of identifying the bioactive compound, the number of papers tentatively attributing the biological activity of Kalanchoe extracts to flavonoids or to flavonoid-enriched fractions is increasing nowadays. In a study on the activity of K. pinnata in a mice model of lupus arthritis, the authors observed that the ethyl acetate fraction (rich in quercetin glycosylated flavonoids), obtained from a leaf aqueous extract, inhibited the progression of the disease [ 54 ]. This fraction also produced positive effects on anti-Smith antibody and T reg in lupus mice [ 55 ].…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%
“…In a study on the activity of K. pinnata in a mice model of lupus arthritis, the authors observed that the ethyl acetate fraction (rich in quercetin glycosylated flavonoids), obtained from a leaf aqueous extract, inhibited the progression of the disease [ 54 ]. This fraction also produced positive effects on anti-Smith antibody and T reg in lupus mice [ 55 ]. Still regarding K. pinnata , ethyl acetate fractions enriched in quercetin, luteolin, isorhamnetin, and luteolin-7-glucoside ameliorated oxidative imbalance in neurotoxicity caused by aluminum chloride in rats, showing a neuroprotective effect [ 56 ].…”
Section: Main Classes Of Bioactive Compounds In Kalanchoe ...mentioning
confidence: 99%